2010
DOI: 10.1007/s12663-010-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of oral multiple primary cancer including Spindle Cell Carcinoma

Abstract: Spindle Cell Carcinoma (SPCC) is a relatively rare tumour that is classified as a subtype of squamous cell carcinoma (SCC). Histologically, SPCC is composed of a SCC region and epithelium-derived spindle cells with mesenchymal differentiation. We encountered an interesting case of multiple cancer including SPCC. A histopathologically atypical papillary lesion was found 13 years before our initial examination. Multiple verrucous leukoplakia later developed in the oral mucosa, for which an oral vitamin A derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Systemic symptoms, for instance, generalized weakness, weight loss, abdominal pain, anemia, and fever were complained by selected patients (Howard et al, 2007; Shibuya et al, 2000). Twenty‐four cases had cervical lymph node metastasis upon treatment (Bavle et al, 2016; Jayaram & Elsayed, 2005; Kato et al, 2010; Munakata et al, 1998; Ohba et al, 2015; Ramesh et al, 2019; Reyes et al, 2015; Shigeta et al, 2015; Stojadinovic et al, 2002; Su et al, 2006; Wen‐cheng et al, 2005). Thirteen patients had a prior history of cancer, and 8 patients had prior oral SCC (Gorsky & Epstein, 1998; Kato et al, 2010; Okuyama et al, 2017; Xie et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic symptoms, for instance, generalized weakness, weight loss, abdominal pain, anemia, and fever were complained by selected patients (Howard et al, 2007; Shibuya et al, 2000). Twenty‐four cases had cervical lymph node metastasis upon treatment (Bavle et al, 2016; Jayaram & Elsayed, 2005; Kato et al, 2010; Munakata et al, 1998; Ohba et al, 2015; Ramesh et al, 2019; Reyes et al, 2015; Shigeta et al, 2015; Stojadinovic et al, 2002; Su et al, 2006; Wen‐cheng et al, 2005). Thirteen patients had a prior history of cancer, and 8 patients had prior oral SCC (Gorsky & Epstein, 1998; Kato et al, 2010; Okuyama et al, 2017; Xie et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four cases had cervical lymph node metastasis upon treatment (Bavle et al, 2016; Jayaram & Elsayed, 2005; Kato et al, 2010; Munakata et al, 1998; Ohba et al, 2015; Ramesh et al, 2019; Reyes et al, 2015; Shigeta et al, 2015; Stojadinovic et al, 2002; Su et al, 2006; Wen‐cheng et al, 2005). Thirteen patients had a prior history of cancer, and 8 patients had prior oral SCC (Gorsky & Epstein, 1998; Kato et al, 2010; Okuyama et al, 2017; Xie et al, 2017). Particularly, two patients had multiple oral SCC recurrences before they were diagnosed with intraoral SpCC (Kato et al, 2010; Xie et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,12,16,28 The utility of adjuvant radiotherapy in HNSpCC has been doubted because studies have reported high mortality in irradiated patients. 12,16,17,22,24,28,29,37,38,[55][56][57][58][59][63][64][65][66][67][68][69][70][71] Of importance, many studies demonstrating disappointing responses to radiotherapy were either of limited size and scope, sampled nonrepresentative populations, or failed to include data necessary for making definitive inferences about treatment and outcomes. 6 To our knowledge, our study is the first to report that treatment with surgery + radiotherapy and surgery + chemoradiotherapy both provide independent survival benefits in HNSpCC when compared with treatment with surgery alone, after adjusting for patient, tumor, and treatment characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival of SpCC is poorer than SCC [12]. Surgical resection with neck dissection is accepted as the best treatment of choice in the oral cavity [4, 7] and is aimed at controlling local and distant recurrence [11].…”
Section: Discussionmentioning
confidence: 99%